Hydrolysis of tumor cell lipids after CTL-mediated death - Alves, Bryce (Oxford University Press, 2009)
Contributions of lipases to CTL function have been debated, including if T cell lipases damage target cells. Expression of the lipase pancreatic lipase-related protein 2 (PLRP2) was previously found in IL-4 cultured lymphocyte cell lines but absent from IL-2 cultured lymphocytes. Here, we evaluated IL-2 and IL-4 induced CTLs for hydrolysis of target cell lipids and killing. Using anti-CD3 redirected lysis of [(3)H]-oleic acid-labeled P815 tumor cells, we detected the release of the radioactive fatty acid (FA). When PLRP2(+/+) and PLRP2(−/−) CTLs were compared, there was more killing by the PLRP2(+/+) CTLs. However, [(3)H]-oleic acid release was similar per dead P815, suggesting that lipid hydrolysis was produced by the dead P815s rather than by PLRP2. The FA release and death were completely dependent on perforin and also occurred when P815s were killed by perforin-containing T cell granule extracts that lacked lipase activity. Death by the cytotoxic granules extracts was unaffected by the addition of lipases. A lipase inhibitor, tetrahydrolipstatin, blocked FA release without affecting CTL-mediated cytotoxicity. Also, CTL-mediated death caused as much FA release as death by disruption of cells by freeze–thawing. The released oleic acid may be sufficient to promote secondary apoptotic responses after CTL-induced trauma.